Targeting Hsp70 Immunosuppressive Signaling Axis with Lipid Nanovesicles: A Novel Approach to Treat Pancreatic Cancer - Kaynak, Ahmet; Vallabhapurapu, Subrahmanya D; Smith, Eric P; Davis, Harold W; Lewis, Clayton S; Ahn, Joseph; Muller, Petr; Vojtesek, Borek; Stringer, Keith F; Franco, Robert S; Bogdanov, Vladimir Y; Shao, Wen-Hai; et al. (Cancers, 2025)
BACKGROUND: Despite many efforts to effectively treat PDAC, PDAC carries one of the highest mortality rates of all major cancers. Thus, there is a critical unmet need to develop novel approaches to improve the clinical outcome of PDAC. It is well known that many cancers, including PDAC, generate a local TME that allows cancer to escape normal immune surveillance. Phosphatidylserine (PS), a negatively charged phospholipid that is abundant on the cancer cell membrane and with known actions to promote the secretion of immunomodulatory proteins, may provide a mechanism to regulate the TME. This study explored that possibility. METHODS: MΦ differentiation and polarization were assessed by Western blotting and flow cytometric approaches. PS exposure and surface markers were analyzed by flow cytometry. Protein-protein and protein-lipid interactions were analyzed by immunofluorescence and enzyme-linked immunosorbent assay (ELISA). Phospholipid and SapC-DOPG treatment were employed to assess target protein functions in MΦ polarization, tumor growth, and survival in subcutaneous and orthotopic tumor models. The PK-PD and safety of SapC-DOPG were tested on orthotopic mouse models. RESULTS: Our studies show that PDAC secretes Hsp70 that stimulates the MΦ polarization to the immunosuppressive M2 phenotype. We found that high surface PS on cancer cells correlates with increased secretion of Hsp70 and is associated with higher MΦ differentiation activity in vitro and in vivo. Furthermore, blocking cancer cell-secreted Hsp70 with SapC-DOPG reverses the immune suppression and reduces tumor growth. CONCLUSIONS: These preclinical results reveal a novel immunotherapeutic approach to potentially improve the outcome of PDAC treatment in humans.
Keywords: pancreatic cancer; immunotherapy; Saposin C-coupled dioleoylphosphatidylglycerol (SapC-DOPG); phosphatidylserine; dioleoylphosphatidylglycerol (DOPG); targeting therapy; M2 macrophage polarization; cancer cell-secreted Hsp70